DEALING WITH THE RISK OF NATURAL HAZARDS THROUGH NETWORKS OF PLANNERS – THE CASE OF KLIMAFIT (2013)
ABSTRACTNetworks and networking are important for dealing with the risk of natural hazards. However, up to now, it is an open question which types of networks contribute to planning and risk management under certain circumstances. The paper focuses on the type of a goal-oriented network. It uses evidence from a case study about a network of planners, mainly regional planners, in the Dresden region in Germany. The distinction between goal orientation and goal directedness is used to show the following: goal directedness of networks involves intensive and continuous processes of sense making (Weick, 1995) to specify the network goal. The governance form of a lead organization network facilitates goal specification.RESUMENRedes y networking son importantes para hacer frente a los riesgos asociados a los peligros naturales. Sin embargo, hasta ahora, aún es una pregunta abierta en cuanto a qué tipos de redes contribuyen a la planificación y gestión del riesgo en determinadas circunstancias. El artículo se centra en un tipo de red con objetivos. Utiliza los resultados de un estudio de caso de una red de diseñadores planificadores, principalmente planificadores regionales, en la región de Dresden, Alemania. La distinción entre la meta a seguir y aquello que orienta esta meta (la directriz) se utiliza para demostrar lo siguiente: las directrices de las redes involucran un proceso continuo e intenso de construcción de sentido (Weick, 1995) que determina el objetivo de la red. La gestión y dirección de una red organizacional en forma de gobernanza, facilita la definición de los objetivos.